2022
DOI: 10.1089/tmj.2021.0584
|View full text |Cite
|
Sign up to set email alerts
|

Role of Newly Introduced Teledentistry Service in the Management of Dental Emergencies During COVID-19 Pandemic in Qatar: A Cross-Sectional Analysis

Abstract: Introduction: The lockdown imposed by the COVID-19 pandemic rendered teledentistry (TD) necessary to maintain the continuity of oral health services and avoid missing emergency dental conditions, while minimizing face-to-face visits. Our objective was to evaluate the ability of a newly introduced triage-based TD service to deliver its goals, by evaluating its processes and outcomes and assessing the demand for TD. Methods: This cross-sectional report assessed the triage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…14 By contrast, reductions in dental antibiotic prescribing at the start of pandemic restrictions were reported in primary dental care in Australia (20%) 15 and in Qatar, only 7% of patients managed remotely with teledentistry were prescribed antibiotics. 16 In France, a similar increase (17%) was experienced in 2020 compared to 2019. 17 Further research is indicated to understand the reasons for these differences between countries.…”
Section: Discussionmentioning
confidence: 75%
“…14 By contrast, reductions in dental antibiotic prescribing at the start of pandemic restrictions were reported in primary dental care in Australia (20%) 15 and in Qatar, only 7% of patients managed remotely with teledentistry were prescribed antibiotics. 16 In France, a similar increase (17%) was experienced in 2020 compared to 2019. 17 Further research is indicated to understand the reasons for these differences between countries.…”
Section: Discussionmentioning
confidence: 75%
“…Results of this study further aim to inform a better designed and accessible information campaign. There is merit in utilising information technology and virtual dentistry clinics that are not limited by the quarantine restrictions for early identification of dental problems associated with psychological distress in children (Ali et al 2022). In addition, the utilisation of mHealth (in means of text messages and phone applications) is regarded as a promising adjunct clinical tool for spreading awareness and health education aiming at preventing and promoting oral health during the pandemic (Luzzi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…All hotline teledentists were trained, had dedicated workspaces for caller privacy and were required to complete a teledentistry data form for each call. Special algorithms were designed to categorize triage levels to assist hotline dentists in managing self-reported complaints (126). The algorithms enabled teledentists to arrive at a diagnosis and decide on who should receive face-to-face dental treatment including emergencies or remote care with courier deliveries of medication.…”
Section: Projectsmentioning
confidence: 99%